640-SLICE CT CORONARY ANGIOGRAPHY IN THE EARLY POSTOPERATIVE PERIOD AFTER CIRCUMFLEX ARTERY STENTING IN A PATIENT WITH ANOMALOUS ORIGIN OF THE RIGHT CORONARY ARTERY FROM THE LEFT SINUS OF VALSALVA - S. K. Ternovoy; N. S. Serova; O. S. Kondrashina; S. A. Kondrashin; V. V. Koblikov; S. A. Suchkova (Вестник рентгенологии и радиологии)
The paper describes a clinical observation showing the capabilities of three-dimensional dynamic 640-slice CT coronary angiography in the postoperative period after coronary artery stenting and in the presence of anomalous origin of coronary arteries from a single coronary sinus. Patient K. aged 76 years who had sought medical advice for his complaints of pressing retrosternal pain radiating to the inter-scapular region when walking 20–30 meters, as well as intermittent episodes of crushing pain at rest was examined. The patient underwent coronary angiography, circumflex artery stenting, and three-dimensional dynamic 640-slice CT-coronary angiography in the early postoperative period. Three-dimensional dynamic 640-slice CT coronary angiography after circumflex artery stenting could determine the status of the operated artery and stent and identify a variant of anomalous origin of the right coronary artery, which had not been previously diagnosed using two invasive coronary angiographies.